Transfer and Metabolism of Triadimefon Residues from Rape Flowers to Apicultural Products - Ying-Hong Li; Bei-Lei Zhou; Ming-Rong Qian; Qiang Wang; Hu Zhang (Journal of Analytical Methods in Chemistry)
This paper presents a study on the transfer and metabolism of triadimefon residues from rape flowers to apicultural products. In the field trials, honeybee colonies were placed in four rape greenhouses treated with triadimefon on standard dosage. Apicultural products (pollen, honey, and royal jelly) were collected on a regular basis. Sample preparation and extraction procedure were established. HPLC/ESI-MS/MS method was validated. The respective residues of triadimefon and metabolite triadimenol were 0.03±0.002 mg/kg and 0.13±0.02 mg/kg in pollen on the 18th day, and both had reached the limits of detection in honey on the 24th day, while they were 0.004±0.0005 mg/kg and 0.010±0.0002 mg/kg in royal jelly on the 22nd day. Mathematical curve fitting studies were further investigated. On the basis of recommended dosage, the degradation half-lives of triadimefon in pollen, honey, and royal jelly were about 0.7, 12.5, and 19.5 days, respectively. Transfer of triadimefon residues from rape flowers to apicultural products diminished over spraying time. The residues of triadimefon and metabolite triadimenol in pollen were about 10 times higher than those in honey and jelly. Time to attain the maximum permissible limit of pollen in the European Union was 14.9 days, predicted from the index function.